1995
DOI: 10.1038/ki.1995.444
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the biochemical mechanism of maleic acid-induced Fanconi syndrome

Abstract: Maleic acid administration is known to produce the Fanconi syndrome, although the biochemical mechanism is incompletely understood. In this study the effect of a single injection of maleic acid (50 mg/kg body wt, i.v.) on the rat renal ATPases was examined. Maleic acid rapidly caused bicarbonaturia, natriuresis, and kaliuresis. When nephron segments were microdissected, there was an 81 +/- 2% reduction in proximal convoluted tubule (PCT) Na-K-ATPase activity (P < 0.005) and a 48 +/- 4% reduction in PCT H-ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 16 publications
4
46
2
Order By: Relevance
“…Decreased activity of the Na + /K + -ATPase leads to impaired membrane recycling activity and this was also observed in our model with carboplatin intoxication. As it is evident from Table 2, renal Na + /K + -ATPase activity was significantly reduced which stands in rank with other studies suggesting that renal insult lead to reduced Na + /K + -ATPase activity (Eiam-ong et al, 1995;Thevenod and Friedmann, 1999). We observed similar findings with the activity of other ATPases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Decreased activity of the Na + /K + -ATPase leads to impaired membrane recycling activity and this was also observed in our model with carboplatin intoxication. As it is evident from Table 2, renal Na + /K + -ATPase activity was significantly reduced which stands in rank with other studies suggesting that renal insult lead to reduced Na + /K + -ATPase activity (Eiam-ong et al, 1995;Thevenod and Friedmann, 1999). We observed similar findings with the activity of other ATPases.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, this transport is effected by Na + -coupled mechanisms involving the Na + /K + -ATPase which maintains the low levels of intracellular low Na + levels essential for successful Na + -coupled (Eiam-ong et al, 1995). Decreased activity of the Na + /K + -ATPase leads to impaired membrane recycling activity and this was also observed in our model with carboplatin intoxication.…”
Section: Discussionmentioning
confidence: 54%
“…The biochemical mechanism responsible for maleic acid-induced alterations in renal tubular function is not completely understood, but it has been suggested that a decrease in Na þ , K þ -ATPase in proximal renal tubules underlies the many consequences of this model of Fanconi syndrome [Eiam-ong et al, 1995]. Under our experimental conditions, however, maleic acid did not show any effect on cellular viability.…”
Section: Fig 4 Upregulation Of Hgf Gene Expression By Maleic Acid Acontrasting
confidence: 45%
“…Maleic anhydride can be completely hydrolyzed to maleic acid (MA) at room temperature with a relative humidity of 96% (Rosenfel and Murphy, 1967). Harrison and Harrison (1954), Albander et al (1982), and Eiamong et al (1995) reported that MA could cause kidney effects to rats and dogs. The symptom is similar to the Fanconi syndrome in human, which the tubular reabsorption is malfunctioned, and glucose, amino acids, phosphate and bicarbonate could not be reabsorbed in proximal tubule (Albander et al, 1982;Harrison and Harrison, 1954).…”
Section: Introductionmentioning
confidence: 99%